Trans-Parasocial Relationship on TikTok Live Shopping: A Netnography Study of Streamers and Audiences Interactions - Azizah Laurensia; Niken Febrina Ernungtyas (Green Publisher Indonesia, 2024)
Social media live shopping has grown rapidly and become common in Indonesian e-commerce since 2020. The development of live and real-time interactions between streamers and audiences establishes trans-parasocial relationships. The relationship is an extension of the parasocial concept, where this seemingly reciprocal relationship occurs between streamers and their audience. This study aims to explore the processes and patterns of forming trans-parasocial relationships between streamers and audiences during TikTok Shop live shopping sessions in Indonesia. This study employs a qualitative method with a netnography study conducted during TikTok Shop live session and post-session comments on X/Twitter. The data include verbal statements from the streamers and audiences on the chat sections, as well as the audience’s posts with keywords related to streamers on platform X/Twitter. Based on data categorization analysis, this study identifies five aspects of the formation of trans-parasocial relationships; (1) building proximity, (2) engaging in self-disclosure, (3) addressing personal acquaintances, (2) receiving audiences’ responses, and (5) creating a reciprocal interaction. The proximity between streamers and audiences can be virtually built by both parties by incorporating conversations about topics rather than products during live sessions. The formation of trans-parasocial relationships leads the audience to keep watching TikTok live shopping and could become a strategic online marketing communication method.